2017
DOI: 10.1111/jace.14891
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the solidification of stainless steel slag and dust mixtures

Abstract: The solidification of a multicomponent stainless steel slag and dust composite has been studied by thermodynamic calculations using Factsage and analyses of samples using EPMA and Rietveld refinement of synchrotron X-ray powder diffraction after various cooling rates. At an apparent cooling rate of 1 K/min, the content of spinel (10.6 wt%) was less than thermodynamically calculated (16.6 wt %), largely because of difficulties in the diffusion of depleted ions (including Cr, Mn, and Ni) in the liquid with very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The other relatively recent area of research is selective Cr concentration into a predefined primary crystal phase and the subsequent phase separation of the Cr‐containing slags through controlled cooling. This third approach is in line with sustainable process development and makes full use of the residual heat of metallurgical slags by modifying the slags at high temperatures 2,12‐14 . This treatment includes the selective nucleation and growth of Cr‐containing primary and secondary crystals and subsequent gravity separation or magnetic separation methods.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The other relatively recent area of research is selective Cr concentration into a predefined primary crystal phase and the subsequent phase separation of the Cr‐containing slags through controlled cooling. This third approach is in line with sustainable process development and makes full use of the residual heat of metallurgical slags by modifying the slags at high temperatures 2,12‐14 . This treatment includes the selective nucleation and growth of Cr‐containing primary and secondary crystals and subsequent gravity separation or magnetic separation methods.…”
Section: Introductionmentioning
confidence: 98%
“…Approximately 15 million tons of Cr‐containing slags classified as environmentally hazardous byproducts are generated annually worldwide during the production of stainless steel, and most of the slags are directly discharged to the environment 1‐4 . Under typical weathering conditions, the direct discharge of Cr‐containing slags into the environment will eventually result in Cr dissolution into water and soil (4Cr 3+ + 10H 2 O + 3O 2 = 4CrO 4 2− + 20H + ), damaging the ecology, hindering animal and plant growth and causing various diseases as Cr 6+ enters the human body through the digestive tract and skin 5‐7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies on the solidification of a multicomponent stainless steel slag have been studied to obtain a high yield ratio of valuable elements. 20,21) The effect of the slag composition on the formation of spinel-type inclusions has been investigated to improve the purity of liquid steel. [22][23][24][25] Formation of V-rich spinel phase in CaO-SiO 2 -MgO-FeO t -Al 2 O 3 -V 2 O 3 -P 2 O 5 slags at 1 573 K has been discussed to separate the vanadium-concentrating phase.…”
Section: Crystallization Behavior and Growth Mechanisms Of Spinel Crymentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] The consensus of these researches is to selectively concentrate the potentially hazardous Cr in a primary crystal spinel phase by controlling the crystallization during the solidification of molten stainless steel slags, which generally exists as a complex spinel (Mg,Fe,Mn,Ni)(Cr,Fe,Al,Ni) 2 O 4 dependent on the type of elements in the stainless steel slags and is significantly diluted in Cr making it uneconomical for subsequent retrieval. [12][13][14][15][16] In addition to the relatively low content of Cr in the complex spinel, which is not conducive to selective enrichment and recovery of Cr, studies on the leaching behavior of modified slags are limited. Samada et al 18 suggested that some portion of Cr can remain in the unstable Ca 2 SiO 4 phase and be released during the elution of stainless steel slags with seawater.…”
Section: Introductionmentioning
confidence: 99%